Diverse Profile of Fermentation Byproducts From Thin Stillage - Fortney, Nathaniel W.; Hanson, Nathaniel J.; Rosa, Paula R. F.; Donohue, Timothy J.; Noguera, Daniel R. (Frontiers in Bioengineering and Biotechnology, 2021)
The economy of biorefineries is influenced not only by biofuel production from carbohydrates, but also by the production of valuable compounds from largely underutilized industrial residues. Currently, the demand for many chemicals that could be made in a biorefinery, such as succinic acid, medium-chain fatty acids, and lactic acid is fulfilled using petroleum, palm oil, or pure carbohydrates as raw materials, respectively. Thin stillage, the residual liquid material following distillation of ethanol, is an underutilized coproduct from the starch biofuel industry. This carbon-rich material has the potential for chemical upgrading by microorganisms. Here we explored the formation of different fermentation products by microbial communities grown on thin stillage using different bioreactor conditions. At the baseline operational condition (6 days retention time, pH 5.5, 35 °C) we observed a mixture of medium-chain fatty acids as the principal fermentation products. Operation of a bioreactor with a 1-day retention time induced an increase in succinic acid production, and a temperature increase to 55 °C resulted in the accumulation of lactic and propionic acids. In addition, a reactor operated with a 1-day retention time at 55 °C conditions resulted in lactic acid accumulation as the main fermentation product. The prominent members of the microbial community in each reactor were assessed by 16S rRNA gene amplicon sequencing and phylogenetic analysis. Under all operating conditions, members of the Lactobacillaceae family within Firmicutes and the Acetobacteriaceae family within Proteobacteria were ubiquitous. Members of the Prevotellacea family within Bacteroidetes and Lachnospiraceae family within the Clostridiales order of Firmicutes were mostly abundant at 35 °C and not abundant in the microbial communities of the thin stillage reactors incubated at 55 °C. The ability to adjust bioreactor operating conditions to select for microbial communities with different fermentation product profiles offers new strategies to explore and compare potentially valuable fermentation products from thin stillage, and allow industries the flexibility to adapt and switch chemical production based on market prices and demands.